2010
DOI: 10.14267/veztud.2010.11.02
|View full text |Cite
|
Sign up to set email alerts
|

A Miles és Snow-féle stratégiatipológia kutatási kérdései (Research issues of Miles and Snow strategic typology)

Abstract: Jelen dolgozat a Miles és Snow (1978) által kidolgozott stratégiai tipológiával kapcsolatos legjelentősebb kutatások megállapításait igyekszik összefoglalni. A szerző az elmúlt három évtized Miles és Snow-i kutatásaiban leginkább érintett területek alapján osztályozza a feldolgozott cikkeket, majd részletesen ismerteti a Kutató, Elemző, Védekező és Reagáló stratégiát követő vállalatokra vonatkozó marketing- és teljesítményimplikációkat. A vizsgálatok korlátainak és hiányosságainak feltárását követően a Miles é… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Generally, the data suggest that prospectors (represented by focusing on new product development and/ or new customer groups) dedicate more attention to BPI than defenders and analysers. These findings are partially supported and are consistent with extant literature (Porter, 1980;Walker & Reukert, 1987;Augusto et al, 2014;Zahra, 1994;Berthon et al, 1999;Csepeti, 2010). For instance, Augusto et al (2014) found that product innovation differentiation affects each type of innovation positively, which also suggests a strong impact of new product focus.…”
Section: Discussionsupporting
confidence: 88%
“…Generally, the data suggest that prospectors (represented by focusing on new product development and/ or new customer groups) dedicate more attention to BPI than defenders and analysers. These findings are partially supported and are consistent with extant literature (Porter, 1980;Walker & Reukert, 1987;Augusto et al, 2014;Zahra, 1994;Berthon et al, 1999;Csepeti, 2010). For instance, Augusto et al (2014) found that product innovation differentiation affects each type of innovation positively, which also suggests a strong impact of new product focus.…”
Section: Discussionsupporting
confidence: 88%